Determination of N* amplitudes from associated strangeness production in p+p collisions - Münzer, Robert Helmut; Herrmann, Norbert; Deppner, Ingo Martin; Zinyuk, Victoria (Physics letters, 2018)
We present the first determination of the energy-dependent amplitudes of N⁎ resonances extracted from their decay in KΛ pairs in p+p→pK+Λ reactions. A combined Partial Wave Analysis of seven data samples with exclusively reconstructed p+p→pK+Λ events measured by the COSY-TOF, DISTO, FOPI and HADES Collaborations in fixed target experiments at kinetic energies between 2.14 to 3.5 GeV is used to determine the amplitude of the resonant and non-resonant contributions into the associated strangeness final state. The contribution of seven N⁎ resonances with masses between 1650 MeV/c2 and 1900 MeV/c2 for an excess energy between 0 and 600 MeV has been considered. The Σ-p cusp and final state interactions for the p-Λ channel are also included as coherent contributions in the PWA. The N⁎ contribution is found to be dominant with respect to the phase space emission of the pKΛ+ final state at all energies demonstrating the important role played by both N⁎ and interference effects in hadron-hadron collisions.